2019
DOI: 10.1111/jop.12960
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of thalidomide on the recurrence interval of continuous recurrent aphthous ulceration: A randomized controlled clinical trial

Abstract: Background: Recurrent aphthous ulceration (RAU) is the most common oral mucosal disease. Some patients have almost continuous oral ulcers which influence the quality of life. The aim of this study was to observe the efficacy and safety of thalidomide on the recurrence interval of continuous RAU. Methods:A randomized controlled clinical trial was designed, and 60 continuous RAU patients were randomly assigned to the experimental group (n = 32, taking thalidomide before bed at a dose of 100 mg/d for 10 days, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 27 publications
0
31
0
3
Order By: Relevance
“…An increasing number of studies using animal models have shown that THD can ameliorate OM induced by chemotherapy and/or radiotherapy 13,14 . THD has also been demonstrated to be beneficial in the treatment of oral ulcers in patients with recurrent aphthous ulceration, HIV infection, or Behçet syndrome 15‐17 . Furthermore, our previous clinical observational study also found that THD could decrease the occurrence and severity of OM in patients with NPC 18 .…”
Section: Introductionmentioning
confidence: 87%
“…An increasing number of studies using animal models have shown that THD can ameliorate OM induced by chemotherapy and/or radiotherapy 13,14 . THD has also been demonstrated to be beneficial in the treatment of oral ulcers in patients with recurrent aphthous ulceration, HIV infection, or Behçet syndrome 15‐17 . Furthermore, our previous clinical observational study also found that THD could decrease the occurrence and severity of OM in patients with NPC 18 .…”
Section: Introductionmentioning
confidence: 87%
“…Thalidomide, however, is an immune‐modulatory drug that acts throughout the body through the circulatory system. Previous studies generally believe that thalidomide is by regulating TNF‐α levels to reduce the recurrence rate of RAS 28‐30 . Clinically, we have found that no significant changes in serum TNF‐α were observed after thalidomide was used; on the contrary, the IL‐6 level was significantly decreased.…”
Section: Discussionmentioning
confidence: 53%
“…For instance, short-term administration of prednisone (eg, for 2 weeks) should produce fewer side effects. 14,15 On the other hand, it is likely that the total doses of oral thalidomide cause adverse reactions. As such, low-dose thalidomide should be better tolerated in patients.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Thalidomide has been shown to be an effective systemic drug in the treatment of refractory oral ulceration, with growing evidence regarding its efficacy in the management of RAS. [14][15][16][17] The exact mechanism of thalidomide action on oral ulcers remains unknown. Its anti-inflammatory action is believed to derive from modulation of the inflammatory cascade and from interaction with various cytokines, including interleukin (IL)-6, IL-10, and tumor necrosis factorα (TNFα).…”
mentioning
confidence: 99%
See 1 more Smart Citation